Shared leadership, self-management and perceived team effectiveness in the military context - Cakiroglu, S. S.; Caetano, A.; Costa, P. (Military Psychology, 2021)
Although there are many studies of leadership in military teams, few have focused on military team factors that could be linked to shared leadership in an international military staff. The focus of shared leadership is on team members’ interacting in order to lead collectively by sharing leadership tasks, rather than on an individual being a sole leader. The aim of this study is to identify predictors of a positive attitude toward shared leadership in the context of military teams, and how they are related to perceived team effectiveness. Results show that task complexity is the critical predictor of a positive attitude toward shared leadership, and that attitude toward shared leadership is positively related to perceived team effectiveness through self-management in a military context. What is more, when self-management is low in military teams, trust compensates to increase the perceived effectiveness. The findings contribute to the literature on attitude toward shared leadership in the specific context of international military teams.